2017
DOI: 10.5194/acp-17-10037-2017
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities of Amazonian clouds to aerosols and updraft speed

Abstract: Abstract. The effects of aerosol particles and updraft speed on warm-phase cloud microphysical properties are studied in the Amazon region as part of the ACRIDICON-CHUVA experiment. Here we expand the sensitivity analysis usually found in the literature by concomitantly considering cloud evolution, putting the sensitivity quantifications into perspective in relation to in-cloud processing, and by considering the effects on droplet size distribution (DSD) shape. Our in situ aircraft measurements over the Amazon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 52 publications
4
45
0
Order By: Relevance
“…Vertical velocity increases supersaturation but does not appear to modulate droplet size. Cecchini et al (2017a) also found that different flights demonstrated a small correlation between vertical motion and droplet size. Nevertheless, cloud droplet concentrations are more linearly related to vertical motion (the correlation coefficient is approximately 0.6).…”
Section: Rainfall Sensitivity To Surface Covermentioning
confidence: 86%
See 1 more Smart Citation
“…Vertical velocity increases supersaturation but does not appear to modulate droplet size. Cecchini et al (2017a) also found that different flights demonstrated a small correlation between vertical motion and droplet size. Nevertheless, cloud droplet concentrations are more linearly related to vertical motion (the correlation coefficient is approximately 0.6).…”
Section: Rainfall Sensitivity To Surface Covermentioning
confidence: 86%
“…The high number of flight hours inside growing cumulus clouds allowed for a sensitivity analysis of aerosol concentrations and the thermodynamic effects of such concentrations in the warm phase of cumulus clouds. Cecchini et al (2017a) have also demonstrated that a 100 % increase in aerosol concentrations led to an 84 % increase in the concentration of droplets, but the same relative increase in vertical velocity corresponded only to a 43 % change. Braga et al (2017) have compared HALO microphysical probe measurements of cloud droplet concentrations with a parameterization based on CCN and updraft at the cloud base.…”
Section: Knowledge About Cloud Process In the Amazon Acquired Duringmentioning
confidence: 98%
“…Generally, the large aerosol load, its optical properties, and its ability to serve as CCN might already influence cloud properties and stratification of the thermodynamic profile of the atmosphere at both, local and re-10 gional scales (Cecchini et al, 2017a). As mentioned above, the incoming solar radiation was dimmed compared to the days before and after this BB event.…”
mentioning
confidence: 82%
“…The use of CO 2 can introduce large errors because it also has strong surface sources and sinks, which can lead to erroneous estimates of the background concentration, as discussed in detail in Yokelson et al (2013a). A statistical method using multiple fire tracers (Mixed Effects Regression Emission Technique, MERET), which can resolve the problems associated with variable CO 2 background concentrations, has recently been developed (Chatfield et al, 2019). An enhancement ratio can be interpreted as an emission ratio when it is assured that the concentrations of both species X and the reference species have not been affected by chemical production or loss since the emission and that both concentrations have changed proportionally during dilution of the plume with background air.…”
Section: Definitionsmentioning
confidence: 99%